A volcanic explosion of autoantibodies in systemic lupus erythematosus: A diversity of 180 different antibodies found in SLE patients - Yaniv, Gal; Twig, Gilad; Shor, Dana Ben-Ami; Furer, Ariel; Sherer, Yaniv; Mozes, Oshry; Komisar, Orna; Slonimsky, Einat; Klang, Eyal; Lotan, Eyal; Welt, Mike; Marai, Ibrahim; et al. (Autoimmunity reviews, 2015)
Recent research in systemic lupus erythematosus (SLE) yielded new antigens and antibodies in SLE patients. We describe the various autoantibodies that can be detected in patients with SLE. A literature review, using the terms “autoantibody” and “systemic lupus erythematosus”, was conducted to search for articles on autoantibodies in SLE, their target antigens, association with disease activity and other clinical manifestations. One hundred and eighty autoantibodies were so far described in SLE patients. These include autoantibodies that target nuclear antigens, cytoplasmic antigens, cell membrane antigens, phospholipid-associated antigens, blood cells, endothelial cells, and nervous system antigens, plasma proteins, matrix proteins, and miscellaneous antigens. The target of an autoantibody, the autoantigen properties, autoantibody frequencies in SLE, as well as clinical associations, and correlation with disease activity are described for all 180 autoantibodies. SLE is so far the autoimmune disease with the largest number of detectable autoantibodies. Their production could be antigen-driven, the result of a polyclonal B cell activation, impaired apoptotic pathways, or the outcome of an idiotypic network dysregulation.